The Determinant Factor of Paternal Breastfeeding Self-Efficacy after Hospital Discharge: A Cross Sectional Study - Novia Pratiwi; Siti Chodidjah; Mega Hasanul Huda (Indonesian Journal of Global Health Research, 2025)
Breast milk is essential for infant health, providing vital nutrients and supporting immune development. Despite improvements in exclusive breastfeeding rates in Indonesia, challenges persist, particularly in the early days postpartum. Paternal involvement is crucial for successful breastfeeding, yet many fathers express a lack of confidence in their ability to support this process. This study aims to examine the determinants of paternal breastfeeding self-efficacy (PBSE) following hospital discharge, focusing on factors such as delivery type, paternal education, and mental health. A cross-sectional design was employed, targeting fathers whose partners delivered at public hospitals in Jakarta. Data was collected on paternal characteristics and their influence on PBSE, utilizing multiple linear regression analysis to identify significant associations. The analysis revealed that fathers whose partners had vaginal deliveries exhibited significantly higher PBSE (unstandardized B coefficient of 5.2, p < 0.001). Fathers with a high school education or below showed a positive association with PBSE (unstandardized B of 3.4, p = 0.015). Additionally, anxiety and depression negatively impacted PBSE, with unstandardized B coefficients of -0.2 (p = 0.038) and -0.3 (p = 0.021), respectively. Enhancing paternal confidence through targeted educational interventions and addressing mental health concerns is essential for improving breastfeeding practices. These findings underscore the importance of involving fathers in breastfeeding, contributing to better health outcomes for both mothers and infants.